The Meaning of Sexuality for Javaneese Adolecent at Senior High School, North Surabaya - Hilmi Yumni; Siti Nur Kholifah; Asnani Asnani (Jurnal Ners, 2014)
Introduction: One of reproductive health issues on adolescent in developing countries was sexuality. Issues of sexuality was multifactor, such as cultural factors. Cultural barriers affect the socialization of reproductive health and sexual education in adolescents, because it was considered taboo to talk about it.Methods: This study was a qualitative study. The number of informants as many as 10 adolescent students, one community leader, 2 parent of adolescents, 2 teachers. The data shown is obtained from in-depth interviews. Data were then analyzed by using interactive analysis model, including data reduction, data display, and conclusion.Results: The result had shown that 1) perceptions of sexuality was understood as sexual intercourse or physical activity that was driven by the desire to the opposite sex, perceptions about adolescent promiscuity with regard to sexuality was seen as something that very concern because beyond norms and customs, many sexuality information was obtained from school environment such as peers, media, environment (in this case was people around the house) and none got information from the parents, and the norms-values -culture were believed as self-control in activities related to sexuality such as relationship; 2) adolecent’s behavior related to sexuality was associated with relationship and still done normatively, infl uenced by eastern culture, there was no informant who had sexual intercourse before marriage; 3) psychosexual of adolescent, were affected by social relationships in their environment at home, including closeness to parents, norms, values learned at home.Conclusion: Based on the research results can be given suggestions that one of them needed to talk openly about sex and sexuality information to youth.